The role of DNA methylation in placental development and its implications for preeclampsia - Meng, Yizi; Meng, Yimei; Li, Linli; Li, Yuan; He, Jin; Shan, Yanhong (Frontiers in Cell and Developmental Biology, 2024)
Preeclampsia (PE) is a prevalent and multifaceted pregnancy disorder, characterized by high blood pressure, edema, proteinuria, and systemic organ dysfunction. It remains one of the leading causes of pregnancy complications, yet its exact origins and pathophysiological mechanisms are not fully understood. Currently, the only definitive treatment is delivery, often requiring preterm termination of pregnancy, which increases neonatal and maternal morbidity and mortality rates, particularly in severe cases. This highlights the urgent need for further research to elucidate its underlying mechanisms and develop targeted interventions. PE is thought to result from a combination of factors, including inflammatory cytokines, trophoblast dysfunction, and environmental influences, which may trigger epigenetic changes, particularly DNA methylation. The placenta, a vital organ for fetal and maternal exchange, plays a central role in the onset of PE. Increasing evidence suggests a strong association between DNA methylation, placental function, and the development of PE. This review focuses on the impact of DNA methylation on placental development and its contribution to PE pathophysiology. It aims to clarify the epigenetic processes essential for normal placental development and explore potential epigenetic biomarkers and therapeutic targets for PE. Such insights could lead to the development of novel preventive and therapeutic strategies for this condition.